2021
DOI: 10.1088/1475-7516/2021/08/062
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the properties of warm dark matter using the satellite galaxies of the Milky Way

Abstract: The satellite galaxies of the Milky Way (MW) are effective probes of the underlying dark matter (DM) substructure, which is sensitive to the nature of the DM particle. In particular, a class of DM models have a power spectrum cut-off on the mass scale of dwarf galaxies and thus predict only small numbers of substructures below the cut-off mass. This makes the MW satellite system appealing to constrain the DM properties: feasible models must produce enough substructure to host the number of observed Galactic sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 128 publications
(237 reference statements)
0
56
0
Order By: Relevance
“…Sect. 7.10), or on the dark matter mass (Newton et al 2021). We refer the reader to Baugh (2006), Wechsler and Tinker (2018), Somerville and Dave (2015), Vogelsberger et al (2020) for specialised reviews of galaxy formation physics and here simply summarise those techniques most commonly used in largescale dark matter simulations.…”
Section: Connecting Dark Matter To Galaxies and Baryonsmentioning
confidence: 99%
“…Sect. 7.10), or on the dark matter mass (Newton et al 2021). We refer the reader to Baugh (2006), Wechsler and Tinker (2018), Somerville and Dave (2015), Vogelsberger et al (2020) for specialised reviews of galaxy formation physics and here simply summarise those techniques most commonly used in largescale dark matter simulations.…”
Section: Connecting Dark Matter To Galaxies and Baryonsmentioning
confidence: 99%
“…For dark matter-dominated galaxies, measurements of the enclosed central mass or the inner density slope can differentiate between dark matter models. Cold dark matter (CDM) predicts cuspy central density profiles (Navarro et al 2010), while cored central density profiles (Burkert 1995) may be generated in models such as self-interacting dark matter (Spergel & Steinhardt 2000), warm dark matter (Newton et al 2021), fuzzy dark matter (Hu et al 2000), as well as due to baryonic processes (Governato et al 2015). Measurements of the dark matter distributions may also be used to place constraints on the dark matter particle annihilation cross section (e.g., Strigari 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Following Nadler et al (2021c), we scale these constraints to conservatively account for uncertainty in the MW host halo mass, which is known to impact limits on non-CDM models derived from the MW satellite population (e.g., Newton et al 2021). In particular, for each V kick , we compute the value of τ that decreases f DDM by 27% relative to its value at the original τ constraint when evaluated at a peak subhalo mass of 3.2 × 10 8 M .…”
Section: Resultsmentioning
confidence: 99%
“…We now place our DDM results in the context of constraints on other DM models derived from the MW satellite population and discuss implications for smallscale structure observables. We limit our quantitative comparison to the WDM constraints from Nadler et al (2021c) because this study used an identical modeling framework with the exception of the assumed SHMF suppression; however, we note that many other studies have used the MW satellite population to derive WDM constraints (e.g., Macciò & Fontanot 2010;Polisensky & Ricotti 2011;Anderhalden et al 2013;Kennedy et al 2014;Kim et al 2018;Nadler et al 2019a;Newton et al 2021;Dekker et al 2021). 9 Nadler et al (2021c) found that thermal relic WDM masses below 6.5 keV are excluded by the same MW satellite census that we consider at 95% confidence after marginalizing over an identical set of galaxy-halo connection and MW halo mass parameters.…”
Section: Comparison To Constraints On Other Dark Matter Models From M...mentioning
confidence: 99%